Immunotherapy in patients with cervical cancer - A. G. Kedrova (Опухоли женской репродуктивной системы, 2020)
Immunotherapy, also known as therapy with immune checkpoint inhibitors, has shown good results in the treatment of both solid tumors and hematological malignancies. Patients with diseases that were considered incurable earlier now have an opportunity for long-term disease stabilization and high frequency of clinical remissions. This review focuses on clinical benefits and toxicity profiles of immune checkpoint inhibitors used for cervical cancer, as well as on the ways to improve prognosis and indications for immunotherapy. Correct choice of biomarkers for predicting the response to immunotherapy will ensure more precise selection of patients. This review of immunotherapy methods aims to help clinicians with the indications for this relatively new treatment which has revolutionized treatment standards. Immunotherapy has many forms, including oncolytic virus therapy, chimeric antigen receptor T-cell therapy (CAR), cancer vaccines, and adoptive T-cell therapy, in particular, immune checkpoint inhibitors, first generation of which includes monoclonal antibodies against PD-1 (pembrolizumab, nivolumab, and cemiplimab), against PD-L1 (atezolizumab, avelumab, and durvalumab), and against CTLA-4 protein (ipilimumab).